2019
DOI: 10.3390/ijms20020381
|View full text |Cite
|
Sign up to set email alerts
|

Review of Current Strategies for Delivering Alzheimer’s Disease Drugs across the Blood-Brain Barrier

Abstract: Effective therapy for Alzheimer’s disease is a major challenge in the pharmaceutical sciences. There are six FDA approved drugs (e.g., donepezil, memantine) that show some effectiveness; however, they only relieve symptoms. Two factors hamper research. First, the cause of Alzheimer’s disease is not fully understood. Second, the blood-brain barrier restricts drug efficacy. This review summarized current knowledge relevant to both of these factors. First, we reviewed the pathophysiology of Alzheimer’s disease. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 143 publications
(53 reference statements)
0
94
0
3
Order By: Relevance
“…The Coulomb interactions favor the adsorption of positively charged species, for instance, arginine residues. Also of note is that due to the positively charged nature, arginine has been found to enhance the cellular uptake of peptides 18 and promote the therapeutic delivery of peptides across the blood-brain barrier for Alzheimer's disease 19 . Therefore, the observed drops in the RBD-ACE2 binding energy for mutants 1 and 2 could be primarily ascribed to a change in (long-range) Coulomb interactions between ACE2 and the spike protein (Table S2), even though the polybasic cleavage sites are around 10 nm away from the RBD and ACE2.…”
Section: Demonstrated Inmentioning
confidence: 99%
“…The Coulomb interactions favor the adsorption of positively charged species, for instance, arginine residues. Also of note is that due to the positively charged nature, arginine has been found to enhance the cellular uptake of peptides 18 and promote the therapeutic delivery of peptides across the blood-brain barrier for Alzheimer's disease 19 . Therefore, the observed drops in the RBD-ACE2 binding energy for mutants 1 and 2 could be primarily ascribed to a change in (long-range) Coulomb interactions between ACE2 and the spike protein (Table S2), even though the polybasic cleavage sites are around 10 nm away from the RBD and ACE2.…”
Section: Demonstrated Inmentioning
confidence: 99%
“…11 NPs are employed for diverse applications, including sitespecific and targeted drug delivery in cancer, 12 as the leaky and defective architecture of tumour allows interstitial access to NPs which is popularly known as enhanced permeation and retention. 13,14 These are explored for drug delivery through different routes of administration including oral, 15 pulmonary, 16 nasal, parenteral, 17 ocular, 18 brain 19 and dermal-transdermal routes. 20,21 The reports focused on cyclodextrin (CD) which discusses its role in oral cancer therapy, 22 pharmaceutical and biomedical applications of CD-based nanogels 23 and in drug and gene delivery are available.…”
Section: Introductionmentioning
confidence: 99%
“…BBB structure is not the focus of this review, hence some essential key points about this topic are given and the reader is suggested to eventually look through other papers that better present its structure, physiological, immunological and pathological characteristics and BBB overcoming strategies. 9,12,13 In summary, BBB is composed by brain microvascular endothelial cells, pericytes, astrocytes, tight junctions, neurons, and basal membrane that create a continuous barrier whose functions are the protection of the brain and the strict control of the passage of solutes. 14 Molecules that can overcome the BBB through passive diffusion should be liposoluble and generally not charged at physiological pH, should have a <500 Da molecular weight and a partition coefficient between 0.5 and 6.0.…”
Section: Blood-brain Barriermentioning
confidence: 99%